Use of Behavior Change Techniques Alongside Exercise in the Management of Rotator Cuff–Related Shoulder Pain: A Scoping Review. Issue 4 (28th December 2021) - Bourke, Jaryd; Skouteris, Helen; Hatzikiriakidis, Kostas; Fahey, David; Malliaras, Peter
Abstract: Objectives: The aims of this scoping review were to: (1) determine the frequency and types of behavior change techniques (BCTs) and education utilized in trials investigating exercise interventions for rotator cuff related shoulder pain (RCRSP); (2) subcategorize the BCTs and education found in the trials to summarize all behavior change approaches reported by trials; and (3) compare the frequency, types, and subcategories of BCTs and education utilized in the clinical guidelines for managing RCRSP between the trials. Methods: Data sources included Cochrane Central Register of Controlled Trials, Ovid MEDLINE, Ovid EMBASE, CINAHL Plus, Google Scholar and PubMed, which were searched from inception to June 2020. Trials assessing exercise interventions for RCRSP were included. Three authors independently determined eligibility and extracted data. The frequency and types of BCTs and education in the trials and clinical practice guidelines were reported and compared descriptively. Two authors assessed the content of the BCTs to develop subcategories. Results: Most trials reported including at least 1 type of BCT (89.2%), which was most commonly feedback and monitoring (78.5%). There were many different approaches to the BCTs and education; for example, feedback and monitoring was subcategorized into supervised exercise, exercise monitoring, and feedback through external aids, such as mirrors. Clinical guidelines recommend supervision, goal setting, activity modification, pain management recommendations, information about the condition, and exercise education. Conclusion: Although over two-thirds of trials reported including a BCT alongside exercise interventions for RCRSP, the breadth of these interventions is limited (supervision is the only common one). Future trialists should consider using any type of BCT that may improve exercise adherence and outcomes. Impact: The findings of this review have: (1) identified gaps in the literature; and (2) contributed to the design of future exercise interventions for RCRSP.